Complement receptor 1 (CR1, CD35) association with susceptibility to leprosy. - Gabriela Canalli Kretzschmar; Luana Caroline Oliveira; Renato Mitsunori Nisihara; Thirumalaisamy P Velavan; Sérvio Túlio Stinghen; Ewalda R S Stahlke; Maria Luiza Petzl-Erler; Iara José T de Messias-Reason; Angelica Beate Winter Boldt (Public Library of Science (PLoS), 2018)
BACKGROUND:Pathophysiological mechanisms are still incompletely understood for leprosy, an urgent public health issue in Brazil. Complement receptor 1 (CR1) binds complement fragments C3b/C4b deposited on mycobacteria, mediating its entrance in macrophages. We investigated CR1 polymorphisms, gene expression and soluble CR1 levels in a case-control study with Brazilian leprosy patients, aiming to understand the role of this receptor in differential susceptibility to the disease. METHODOLOGY:Nine polymorphisms were haplotyped by multiplex PCR-SSP in 213 leprosy patients (47% multibacillary) and 297 controls. mRNA levels were measured by qPCR and sCR1 by ELISA, in up to 80 samples. PRINCIPAL FINDINGS:Individuals with the most common recombinant haplotype harboring rs3849266*T in intron 21 and rs3737002*T in exon 26 (encoding p.1408Met of the York Yka+ antigen), presented twice higher susceptibility to leprosy (OR = 2.43, p = 0.017). Paucibacillary patients with these variants presented lower sCR1 levels, thus reducing the anti-inflammatory response (p = 0.040 and p = 0.046, respectively). Furthermore, the most ancient haplotype increased susceptibility to the multibacillary clinical form (OR = 3.04, p = 0.01) and presented the intronic rs12034383*G allele, which was associated with higher gene expression (p = 0.043), probably increasing internalization of the parasite. Furthermore, there was an inverse correlation between the levels of sCR1 and mannose-binding lectin (initiator molecule of the lectin pathway of complement, recognized by CR1) (R = -0.52, p = 0.007). CONCLUSIONS:The results lead us to suggest a regulatory role for CR1 polymorphisms on mRNA and sCR1 levels, with haplotype-specific effects increasing susceptibility to leprosy, probably by enhancing parasite phagocytosis and inflammation.